ANALISIS KINERJA SISTEM MONITORING SANTRI DENGAN PENDEKATAN UJI FUNGSIONAL DAN SUS (SYSTEM USABILITY SCALE) - Lucita, Lucita; Rindri, Yang Agita; Farma, Tri Agusti (STMIK KHARISMA Makassar, 2025)
This study aims to analyze the performance of a student monitoring system in Islamic boarding schools using functional testing and the System Usability Scale (SUS) approach. The system is designed to facilitate the management of student data, including violations, achievements, permissions, and health, while providing real-time access for parents. The research employs the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. Functional testing ensures that all features operate according to specifications, while usability evaluation using SUS was conducted with 30 parent respondents. The functional testing results indicate that all main system features function correctly and meet user requirements. Meanwhile, the average SUS score of 80 falls within the Good–Excellent category, demonstrating that the system is easy to use, quickly understandable, and supports effective student management activities. The study concludes that the developed student monitoring system not only fulfills operational functions but also offers high usability, making it an effective tool for improving the efficiency of boarding school management.